The Wage Elasticity of Recruitment - Boris Hirsch; Elke J. Jahn; Alan Manning; Michael Oberfichtner (Institute of Labor Economics (IZA), 2022)
One of the factors likely to affect the market power of employers is the sensitivity of the flow of recruits to the offered wage, but there is very little research on this. This paper presents a methodology for estimating the wage elasticity of recruitment and applies it to German data. Our estimates of the wage elasticity of recruitment are about 1.4. We also report evidence that high-wage employers are more selective in hiring, in which case the relevant recruitment elasticity should be higher, about 2.2. Together with prior estimates of the quit elasticity these results imply that wages are 72–77% of the marginal product of labour. Further, we find lower elasticities for recruits hired from non-employment as well as for women, non-German nationals, non-prime-age workers, less skilled workers, and workers with less complex jobs.
Keywords: J42; J31; 330; monopsony; imperfect labour markets; wage elasticity of recruitment